2023
DOI: 10.1177/20417314231185858
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix-derived peptide stimulates the generation of endocrine progenitors and islet organoids from iPSCs

Abstract: Induced pluripotent stem cells (iPSCs) have enormous potential in producing human tissues endlessly. We previously reported that type V collagen (COL5), a pancreatic extracellular matrix protein, promotes islet development and maturation from iPSCs. In this study, we identified a bioactive peptide domain of COL5, WWASKS, through bioinformatic analysis of decellularized pancreatic ECM (dpECM)-derived collagens. RNA-sequencing suggests that WWASKS induces the formation of pancreatic endocrine progenitors while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…As an indicator for adult stem cells in multiple organs, Lgr5 is expressed in injured and regenerated pancreatic ducts, while Lgr5 + duct cells can produce pancreatic exocrine organoids in vitro and differentiate into ducts and endocrine cells after transplantation induction (Huch et al, 2013). A peptide originating from the extracellular matrix determines the destiny of induced PSCs, leading to the creation of endocrine progenitors and later islet organoids (Heaton et al, 2023) (see Figure 1).…”
Section: Organoids Of Pancreatic Endocrine Glandmentioning
confidence: 99%
“…As an indicator for adult stem cells in multiple organs, Lgr5 is expressed in injured and regenerated pancreatic ducts, while Lgr5 + duct cells can produce pancreatic exocrine organoids in vitro and differentiate into ducts and endocrine cells after transplantation induction (Huch et al, 2013). A peptide originating from the extracellular matrix determines the destiny of induced PSCs, leading to the creation of endocrine progenitors and later islet organoids (Heaton et al, 2023) (see Figure 1).…”
Section: Organoids Of Pancreatic Endocrine Glandmentioning
confidence: 99%
“…[6] Our recent study discovered that a short peptide motif developed from a pancreatic extracellular matrix (ECM) protein is able to boost the glucose sensitivity for glucose responsive insulin secretion from iPSC-derived islets. [7] Nevertheless, generating biologically functional islets that consisting of all major types of islet cells, including 𝛼, 𝛽, 𝛿, and 𝛾 cells remains a significant challenge. It has been reported that decellularized pancreatic materials induce the formation of human islets that harbor all major pancreatic endocrine cell types.…”
Section: Introductionmentioning
confidence: 99%